Autonomy supportive and reactance supportive inoculations both boost resistance to propaganda, as mediated by state autonomy but not state reactance. (1st January 2021) - Wilbur, Douglas; Sheldon, Kennon M.; Cameron, Glen
ABSTRACT: We tested two counter-propaganda strategies for boosting peoples' resistance to extremist propaganda, one based on Self-Determination Theory and one based on Psychological Reactance theory. Caucasian mTurk worker participants (N = 387) were told they would read extremist messages and were randomly assigned to either a neutral control condition, an autonomy-supportive inoculation condition ('it is your choice to agree or not'), or a reactance-supportive inoculation condition ('don't let them manipulate you'). They then read and rated their agreement with two anti-immigrant extremist messages. Both inoculations produced lower agreement with the extremist messages, compared to the control condition. These effects were independent of participants' political conservatism and trait reactance, although these person variables were both associated with message agreement. Both the autonomy-support and reactance-support effects were mediated by felt autonomy need-satisfaction, but not by state reactance. Ironically, telling participants that they are free to accept extremist claims may help them to resist such claims.